2013
DOI: 10.1080/13607863.2013.805730
|View full text |Cite
|
Sign up to set email alerts
|

Marital satisfaction and depressive symptoms among Chinese older couples

Abstract: The MDMD was only partially supported among older couples in China. An asymmetrical pattern of cross-spouse effects was found, suggesting that the husbands' perception of marital dissatisfaction could significantly predict their wives' depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 38 publications
3
41
1
2
Order By: Relevance
“…In addition, both men's and women's own effects and their partner's effects findings are consistent with the literature in that these links were found to be significant (Beach et al., ; Gustavson et al., ). Contrastingly, Miller et al., () and Wang et al., () both found only one path where relationship satisfaction predicted their partner's depressive symptoms; whereas our findings found that both men's and women's relationship satisfaction levels predicted their partner's depressive symptoms across time. In short, these findings on the link between relationship satisfaction and depressive symptoms contributes to the literature on trajectories of depression and expands the literature on depression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, both men's and women's own effects and their partner's effects findings are consistent with the literature in that these links were found to be significant (Beach et al., ; Gustavson et al., ). Contrastingly, Miller et al., () and Wang et al., () both found only one path where relationship satisfaction predicted their partner's depressive symptoms; whereas our findings found that both men's and women's relationship satisfaction levels predicted their partner's depressive symptoms across time. In short, these findings on the link between relationship satisfaction and depressive symptoms contributes to the literature on trajectories of depression and expands the literature on depression.…”
Section: Discussioncontrasting
confidence: 99%
“…When examining the cross‐lag effects between husbands and wives, their earlier reports of marital satisfaction predicted reports of depressive symptoms in their spouse a year later (Beach et al., ). In other studies, only husband's relationship satisfaction predicted their wives depressive symptoms (Wang, Wang, Li, & Miller, ) and wives relationship satisfaction predicted their husbands depressive symptoms (Miller, Mason, Canlas, Wang, Nelson, & Hart, ). It is important to note that both of these studies were cross‐sectional and only found one significant partner path.…”
Section: Trajectories Of Depressive Symptomsmentioning
confidence: 86%
“…Most people experience conflicts in their communications as infinitely intensive (Halford, 2001;HoltLunstad, & Birmingham, 2008). Conflicts are also positively correlated with inappropriate psychological well-being conditions (Galinsky and Waite, 2014;Hawkins, & Booth, 2005), insecure attachment style (Gouin, 2009), several psychiatric disorders such as internalizing disorders (Brock, & Lawrence, 2011), depression (Wang , Wang , & Miller 2014), anxiety disorders (Doss, Simpson, & Christensen, 2004), sexual dysfunction disorders (Metz, & Epstein, 2002), and physical health problems (Galinsky and Waite, 2014) such as hypertension (Holt-Lunstad, & Birmingham, 2008), chronic pain (Cano et al, 2004) and ischemic heart diseases (Galinsky and Waite, 2014). The more unsatisfied the spouses are with their marital status, the higher is the probability of divorce (Gottman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Singapore found that marital dissatisfaction was positively associated with concurrent depressive symptoms (Sandberg, Yorgason, Miller, & Hill, 2012), and a study conducted in China found that wives’ and husbands’ marital dissatisfaction was positively associated with their own and their partner’s depressive symptoms (Miller et al, 2013). However, another study of older married Chinese couples (aged 57 to 88) found that whereas husband’s marital dissatisfaction was positively associated with wives’ depressive symptoms, no association was found between one spouse’s marital dissatisfaction and their own level of depressive symptoms (Wang, Wang, Li, & Miller, 2014). Two studies conducted in Hong Kong also found that poorer marital adjustment and greater dissatisfaction were positively associated with more psychiatric symptoms and midlife crisis symptoms, lower levels of purpose in life, life satisfaction, and perceived health in a cross-sectional (Shek, 1995) and a longitudinal (Shek, 2000) analysis.…”
mentioning
confidence: 99%